A physical quality improvement of special operations force candidates by means of a proprietary program - Maksim Kuznetsov (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the level of preparedness of cadets of the second year of military university - potential candidates for admission to the units of the Special Operations Forces. Material & Methods: experimental material was the official test results of cadets during the admission of current and test standards during the year of their studies at a military high school. Cadets of the second year took part in the experiment. Two groups of 26 cadets were created, identical in terms of physical preparedness. The testing of the physical readiness of the cadets was assessed by the exercises "Manual on physical training in the Armed Forces of Ukraine" (2014): running to different distances, exercises for strength and strength endurance, overcoming the combined arms obstacle course. A program for the development of endurance using the interval method of training is proposed. Results: after training on the proposed program, the results grew by almost 10%, and in the group that trained according to the traditional scheme, the results only increased by 3%. Conclusion: increase in results depends on the organization of the educational process and on the methods of training are used. In the CG the results are largely inferior to the increase in the results in the EG. The proposed program gives a significantly better result.